Characterization of different screened proteins from Chinese honeysuckle leaves and evaluate their antimicrobial potential - Mayank Kulshreshtha; Anuj Kumar Sharma; Yogesh Murti; Vibha; Neeraj Verma; Anita Singh; Soumyadip Mukherjee; Amit Nigam; Manjul Pratap Singh (Elsevier, 2024)
Background: According to Chinese Medicine system, Chinese honeysuckle have a lot of valuable metabolites which have a various potential like anti-inflammatory action, antidiabetic, analgesics, antipyretic, eliminates pollutants etc. It is frequently given for patients with colds that include fever, headaches, and sore throats, but it may also be used to help people who are overheated or under stress chill down. Objective and method: The present study is designed to screen out through SDSPAGE electrophoresis from the various proteins from Chinese honeysuckle (characterized by IR, NMR and mass spectrometry), evaluated their antimicrobial potential by using various microbial species (Bacillus subtilis MTCC 0441 and Escherichia coli MTCC 1573 with renowned standards). Results: Phytochemical analysis of different extracts showed the presence of different primary and secondary metabolite like alkaloids, glycosides, tannins, proteins, saponin, phenolic compounds etc. Various proteins are screened out with different kds weight like 10, 25, 30, 35, 48, 50, 55 and 70. The analytical analysis revealed the presence of various groups, protons etc. in proteins. The range of zone of inhibition was found to be 1.2 ± 0.01 to 14.5 ± 0.21. The maximum activity was found out in 70 kda protein against Bacillus subtilis. Conclusion: The data generated would be useful for the preparation of monograph of the plant. Generated scientific data may open the various doors for new researchers in coming future,